2016
DOI: 10.1039/c6py00822d
|View full text |Cite
|
Sign up to set email alerts
|

Multiblock thermoplastic elastomersviaone-pot thiol–ene reaction

Abstract: We report a facile approach to designing multiblock thermoplastic elastomers using a two-step thiol-ene polyaddition reaction. It is based on the utilization of intermolecular hydrogen bonding of widely available and cost-effective monomer of N, N'-methylenebis(acrylamide) (MBAm) as physical cross-links. Thiol-terminated "soft" prepolymers were first prepared using ethylene glycol dimethacrylate (EGDMA) and an excess of 1,6-hexanedithiol (HDT); subsequently, the thiolterminated prepolymers were further reacted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 51 publications
(63 reference statements)
2
14
0
Order By: Relevance
“…The first transition matched well with the reported transition temperature for monodisperse MBAm hard segments reported by He and coworkers. [34] The increased breadth of the transition for samples containing higher MBAm was also partly attributed to poorer phase separation due to potential competitive hydrogen bonding with the esters in the sugar‐containing segment and the generally shorter sugar‐containing segment length.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The first transition matched well with the reported transition temperature for monodisperse MBAm hard segments reported by He and coworkers. [34] The increased breadth of the transition for samples containing higher MBAm was also partly attributed to poorer phase separation due to potential competitive hydrogen bonding with the esters in the sugar‐containing segment and the generally shorter sugar‐containing segment length.…”
Section: Resultsmentioning
confidence: 99%
“…These results matched closely with variable temperature FTIR studies on MBAm‐containing poly(β‐thioesters) reported by He and coworkers. [34] The appearance of a shoulder in the CO stretch as temperature increased could also indicate that a shift from ordered to disordered hydrogen bonds also occurred. Previous work in our laboratories studying oxamide‐containing copolymer revealed a similar presence of disordered hydrogen bonds with increasing temperature .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thermoplastic elastomers (TPEs) are an important kind of engineering polymers with both thermoplastic and elastomeric properties . They usually comprise ABA triblocks with two incompatible segments, an ambient‐flexible segment (B) between two hard segments (A) that can form physical cross‐links.…”
Section: Introductionmentioning
confidence: 99%